Kombinasi Metode Double Moving Average dan Double Exponential Smoothing dalam Memprediksi Persediaan Suku Cadang Alat Berat - Fauzi, Reza Dwi; Irawan, Muhammad Dedi (Program Studi Teknik Informatika Universitas Pamulang, 2024)
Gudang Cahaya Harapan is a company that provides heavy equipment in the form of excavators, roller vibrators and road graders which will be rented to its partners for a certain period of time. Each fuel filter has various brands and has a different number or code for each heavy equipment. Manual data recording is very vulnerable to damage and loss. Because of problems like this, an information system with forecasting methods is needed that can help predict the inventory needed systematically based on fuel filter usage data during the previous period to help make fuel filter inventory reports more organized. The method used in this information system is a combination of the Double Moving Average method and the Double Exponential Smoothing method. The combination of the Double Moving Average and Double Exponential Smoothing methods can estimate the amount of fuel filtering used well, with a MAPE value of 0.15 (15%) which is considered good on the MAPE scale. This system will help Gudang Cahaya Harapan employees in stock management for future periods.